Biosimilar Biologic Drugs: A Systematic Approach to Development, Manufacturing and Clinical Applications - Aziz-Andersen, Kaiser Jay (Journal of Drug Delivery and Therapeutics, 2020)
This publication addresses biosimilar biologic drugs development and future innovations. Emphasis is placed on quality system approaches to the development and availability of new biosimilar drug products presented in premarket applications. For approvals of new biosimilars, the sponsors of premarket applications must present analytical and biological characterization to demonstrate that a proposed biosimilar drug is highly similar to the licensed reference product. The premarket application protocol requires a sponsor to describe the biosimilar product’s PK/PD clinical data comparing its safety, efficacy, and immunogenicity to that of the licensed reference product. Emphasis is placed on Quality by Design (QbD), Validation, Verification, and c-GMP risk-based monitoring criteria. A brief discussion is presented on risk-benefit assessment that guides the clinical use of the new biosimilar drug product by providing patients organized data and appropriate labeling information in conformance with the new biosimilar drug’s intended clinical use.Keywords: biosimilar biologic drugs, safety, efficacy and immunogenicity, Quality by Design (QbD)